Analysis of Islamic values in the program anti-bullying in Islamic educational institutions - Mutia Ake Prasong; Eko Tuanto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This research aims to identify how anti-bullying program analysis is in accordance with Islamic design and what aspects support the success of anti-bullying programs in Islamic learning institutions. This research uses bibliography research procedures. Sources of information are obtained from novels, newspapers, posts, information, documents and other sources of data that are relevant to research points, both offline and online. Information obtained from library research is analyzed in a qualitative interactive form. This form of information analysis consists of collecting information, reducing information, presenting information, and drawing conclusions. The research results show that the analysis of the anti-bullying program is in accordance with Islamic concepts such as love and empathy, openness and respect for comparison, equality and balanced treatment, antipathy towards violence, learning moral values, social responsibility and the creation of a noble personality. Factors changing customs, the impact of social media, and social pressures can trigger the appearance of bullying attitudes in the area of Islamic learning. Therefore, a holistic approach is needed that combines religious values with modern management concepts to deal with this case. Important aspects that support the success of anti-bullying programs include full support from school management, active participation of students, teacher training and training, participation of older people, use of innovative learning methods, regular supervision and assessment, collaboration with the community, convenient online control. and open communication.